APPLICATION OF NEW HYPERTENSION GUIDELINES TO RENAL TRANSPLANT RECIPIENTS: IMPACT ON CARDIOVASCULAR OUTCOME AND GRAFT SURVIVAL. (June 2018) - Pagonas, N.; Seibert, F.S.; Bauer, F.; Doevelaar, A.; Klein, T.; Babel, N.; Viebahn, R.; Westhoff, T.H.
Abstract : Objective: Background: Based on data of the SPRINT trial, American national guidelines recently reduced the blood pressure goal from 140/90 mm Hg to 130/80 mm Hg for subjects with increased cardiovascular risk, e. g. those with chronic kidney disease. To date it remains elusive whether renal transplant recipients benefit from these goals as well. Design and method: Methods: We performed a retrospective analysis of 877 patients who underwent kidney transplantation between 1997 and 2011 in three transplant centers in Germany (Berlin and Bochum) with a follow-up of 12 - 120 months. Blood pressure was obtained at regular follow-up examinations in the transplant outpatient clinic. Patient and graft survival was defined as composite endpoint. Subjects were stratified according to mean systolic blood pressure values < 130 mmHg, 130–139 mmHg, or > 140 mmHg. Results: Results: Mean SBP of the overall follow-up period was significantly associated with patient and graft survival. Cumulative survival was significantly higher for those patients with a systolic blood pressure (SBP) < 130 mmHg than those with 130–140 mmHg. Survival was lowest in renal transplant recipients with a mean SBP > 140 mmHg. Analogously, mean SBP of the first 12 months posttransplant < 130 mmHg was associated with better cumulative patient and graft survival than higher blood pressure values in Kaplan Maier analyses. Conclusions: Conclusion: Renal transplant recipients who achieve a mean systolic blood pressure < 130 mmHg have a significantly lower mortality and a better allograft outcome than with the conservative blood pressure goal < 140 mmHg. The new blood pressure targets should be considered suitable for renal transplant recipients as well.